Iodometric Determination of Neutral Amino Acids Using Potassium Iodate - Vijayan, Ranjitha; Salian Gujaran, Shruthi; Rai, Nibha; Madavu Lokanatha Rai, Kuriya (Journal of New Developments in Chemistry, 2022)
In this work, we have reported a simple, cost effective and reliable method for the determination of neutral α-amino acids iodometrically by making use of potassium iodate. This volumetric method determines amino acids instantly, thereby greatly reduces the time of determination.
Keywords: HIO3; glycine; alanine; phenyl alanine; Iodometry; Molecular weight.